Photonic topological Chern insulators based on Tellegen metacrystals. (23rd December 2015) - Jacobs, Daniel A; Miroshnichenko, Andrey E; Kivshar, Yuri S; Khanikaev, Alexander B
Abstract: We demonstrate that topologically nontrivial states of light can be engineered in periodic photonic structures containing media with a Tellegen-type bianisotropic response. Whilst in such bianisotropic materials the time-reversal symmetry is broken, they are characterized by an intrinsic magnetic order which does not require macroscopic magnetization. Our design can therefore be considered as a direct analog of the solid state Chern insulator which exhibits a topological order in the absence of an external bias. Numerical simulations of such Tellegen photonic crystals reveal the existence of one-way edge transport at domain walls and perfectly conducting boundaries not sensitive to structural imperfections such as local defects and disorder. We demonstrate a scheme for achieving robust steering of the edge modes by controlling the phase and amplitude of the source.